PENGARUH MEDIA BOOKLET TERHADAP PENGETAHUAN SISWA MENGENAI PENCEGAHAN DIABETES MELITUS (STUDI PADA SMAN 1 BANDUNG KABUPATEN SERANG) - Amanda Aretuza Febriyanti; Neng Ayu Rosita (Jurnal Kesehatan Siliwangi, 2024)
Background: Diabetes mellitus does not only occur in the 30-60 year age group; it has also been observed in a large number of adolescents. Therefore, in an effort to stop the increasing death rate due to diabetes mellitus, education is needed. Education through the use of learning resources in the form of booklets to help students adopt a smart lifestyle. Booklet media is a versatile, attention-grabbing, and powerful type of media. Purpose: this research is to find out how booklet media influences students' understanding of preventing diabetes mellitus at SMAN 1 Bandung, Serang Regency. Methods: Pre-Experiment One Group Pretest-Postest Without Control and the PPE (Planning, Production, Evaluation) media development model are used in this study. One tool used to test knowledge is the questionnaire. The Paired Simple T-Test was employed for data analysis. Results: The research findings indicated that the booklet media developed using the PPE development model was deemed suitable for use in the field after receiving a media test assessment of 96%, a material test of 100%, and a small scale test of 90%. The pretest knowledge level was 52,2%, and the posttest knowledge level results were 83,8%. The Paired Sample T-Test findings indicate a p-value of 0,001. Conclusion: It was determined that the booklet media "Let's Prevent Type II Diabetes Mellitus Smartly" was practical and that it had an impact on students' understanding of the studies conducted at SMAN 1 Bandung, Serang Regency, addressing the prevention of diabetes mellitus.